Is transport poverty socially or environmentally driven? Comparing the travel behaviours of two low-income populations living in central and peripheral locations in the same city. (October 2018) - Lucas, Karen; Philips, Ian; Mulley, Corinne; Ma, Liang
Abstract: The paper presents a study to explore the relationship between travel poverty and social disadvantage at the local geographical level. The main aim of the research was to identify the extent to which the revealed travel behavioural outcomes of the study participants are due to personal social constraints or environmental conditions in their residential locations. Specifically, we sought to identify if the greater access to local amenities and public transport services of inner city residents led to an increase in their daily travel activities when compared with their urban peripheral counterparts. The research analysed data from a personal travel survey and one-day travel diary with 502 adults aged between 16 and 65 years in two different deprived areas in Merseyside, North West England. Our analysis is somewhat hampered by the small sample size, but the modelled results suggest that more trips, and longer journey distances do not necessarily imply greater social inclusion. The geographically weighted regression models (GWR) highlighted that the physical location of where people live within the city is more influential on their trip-making patterns than social determinants such as household income, age, gender, and/or employment status. Street connectivity, the level of bus services and neighbourhood safety were all particularly significant for determining spatial variations in the daily trips that were undertaken, with more trips being undertaken where there was a greater density of street nodes, bus stops and where people felt safer at night. This highlights the need for local transport and urban policymakers to carefully consider and target these micro-scale factors when attempting to introduce transport interventions to reduce social exclusion amongst low-income urban populations.